To Determine the Frequency of Raised C-Reactive Protein in Patients of Acute Pancreatitis (Medical Forum Monthly, 2024)
Objective: To determine the frequency of raised c-reactive protein in patients of acute pancreatitis.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at Surgical Department Jinnah Post Graduate Medical Centre Karachi and Dow University Hospital from January 2013 to June 2014.Materials and Methods: The patients were selected on the basis of clinical features. Take detailed history regarding epigastric and upper abdomen pain. All the patients of either gender with acute abdominal pain presenting to emergency and diagnosed as acute pancreatitis by serum amylase of 1000 units or more were included in the study. Ranson Scoring and C reactive protein levels on admission were noted.Results: A total of 144 patients, both males and females were included in the study. 17(11.80%) out of 144 subjects were males and rest were females 127(88.19%) cases. The minimum age was 25 years and maximum was 60 years but most of the patients were in the range of 40 to 55 years means age was 43+6.7 years. The minimum value was found to be 25 mg/L while maximum was 57 mg/L. Mean CRP was foud to be 32.2+ 11.43 mg/L for that group of patients. All the patients were also categorized as mild and moderate to severe on the basis of Ranson’s criteria. 73% patients were found to have mild disease with rest having moderate to severe disease. Frequency of CRP observed in our study were in 139(96.52%) cases.Conclusion: We concluded that C reactive protein was a useful severity assessment marker in patients with acute pancreatitis and it can be proposed as an important single factor for determining severity of patients presenting with acute pancreatitis.